The prevalence of depressive symptoms in an elderly population and their relation to life situations in home care - Kleisiaris, Christos; Maniou, Maria; Papathanasiou, Ioanna; Sfiniadaki, Adrianna; Collaku, Eda; Koutsoumpa, Chrysa; Sarafis, Pavlos (My University, 2013)
Background: Depression is a common mental disorder manifested by loss of interest or pleasure, feelings of guilt or low self-esteem, disturbed sleep or appetite, low energy and poor concentration. Depression is a normal part of aging, but unfortunately it is very common in the elderly. Aim: The assessment of the subjective disposition of the elderly as reflected in the last week. Design and Methods: The sample consisted of 200 elderly of 4 nursing homes in Heraklion of Crete. The study was conducted with the quantifydescriptive method. Depression was quantified using the Zung Self-Rating Depression Scale (ZSDS). Analysis included the test x2 analysis, the r-Pearson partial correlation coefficient and the calculation of Cronbach's alpha (α). The data analysis was performed using the statistical programme IBM SPSS 19.0. Results: Cronbach's alpha for the ZSDS questionnaire was 0.81. Most of sample were female (64.5%), aged above 80 years (68.5%), with low level of education (90.5%). The prevalence of depressive symptoms was 58.5%. A significant statistically correlation appears in the elderly with cardiovascular diseases (P-value = 0,001), already diagnosed depression (P-value < 0,005), self-care (P-value = 0,001), living with spouse (P-value = 0,011) indicating greater depressive mood. Moreover, loss of child increases the degree of depression (P-value = 0,037). Conclusions: The life situations of elderly such as self-care, loss of child, loneliness and chronic diseases are directly related to appearance of the daily mood. Moreover, depression is related with cardiovascular diseases (CVD).
Keywords: Depression in elderly; Primary care; Zung self-rating depression scale